EFEK VARIASI RADIUS NUKLEON TERHADAP PERSAMAAN KEADAAN BINTANG NEUTRON - Suparti, Suparti; Sulaksono, A.; Mart, T. (Jurnal Spektra, 2014)
The isoscalar parameter of SNM and the isovector parameter of PNM from various nucleon sizes as well as the effects of the fitting on medium density and low density prediction regimes of PNM have been investigated. To this end, we have chosen the cut-off parameter Î² = 0.0005 and Î² = 0.01, with the nucleon radii of 0, 0.66, 0.76, 0.83, and 0.99 fm. The obtained isoscalar parameters are in a good agreement with the result of the DBHF calculation for all nucleon radii used, except for rN = 0.99 fm, which does not fulfill the SNM EOS prediction based on the result of heavy ion collision. On the other hand, the effect of fitting of the parameters outside the upper and lower bounds leads to a disagreement with the experimental result of Danielwicz et al. It is suspected that this could happen due to the limitation of the parameter range Î², as well as the nucleon radius. Keywords: nucleon radius, parameter, equation of state